Position Paper on Road Map for RNA Virus Research in India - Medigeshi, Guruprasad R.; Fink, Katja; Hegde, Nagendra R. (Frontiers in Microbiology, 2018)
The Indian subcontinent with its population density, climatic conditions, means of subsistence, socioeconomic factors as well as travel and tourism presents a fertile ground for thriving of RNA viruses. Despite being pathogens of huge significance, there is very little focus on research into the biology and pathogenesis of RNA viruses in India. Studies on epidemiology and disease burden, risk factors, the immune response to RNA viruses, circulating virus strains and virus evolution, animal models of disease, antivirals and vaccines are strikingly absent. Emerging RNA viruses such as Zika virus, Nipah virus and Crimean-Congo haemorrhagic fever virus are a matter of grave concern to India. Here we summarize the outcome of the India|EMBO symposium on "RNA viruses: immunology, pathogenesis and translational opportunities" organized at Faridabad, National Capital Region, India on March 28-30, 2018. The meeting focused on RNA viruses (non-HIV), and both national and international experts on RNA viruses covered topics ranging from epidemiology, immune response, virus evolution and vaccine trials concerning RNA viruses. The aim of the symposium was to create a road map for RNA virus research in India. Both concrete and tentative ideas pointing towards short-term and long-term goals were presented with recommendations for follow-up at government level.